Historical Review of the Fluid-Percussion TBI Model - Lyeth, Bruce G. (Frontiers in Neurology, 2016)
Abstract: Traumatic brain injury (TBI) is a major health concern worldwide. Laboratory studies utilizing animal models of TBI are essential for addressing pathological mechanisms of brain injury and development of innovative treatments. Over the past 75 years, pioneering head injury researchers have devised and tested a number of fluid percussive methods to reproduce in animals the concussive clinical syndrome. The fluid percussion brain injury technique has evolved from early investigations that applied a generalized loading of the brain to more recent computer controlled systems. Of the many pre-clinical TBI models, the fluid percussion technique is one of the most extensively characterized and widely used models. Some of the most important advances involved the development of the Stalhammer device to produce concussion in cats and the later characterization of this device for application in rodents. The goal of this historical review is to provide readers with an appreciation for the time and effort expended by the pioneering researchers that have led to today’s state of the art fluid percussion animal models of TBI.